The Relationship between Social Support and the Resilience of Drug Addicts Who Are Being Rehabilitated - Indah Virgiartanti, Mutia; Prilisiana Paskahwati, Irma (Lafadz Jaya Publisher, 2024)
This research aims to determine the relationship between social support and the resilience of drug addicts who are undergoing rehabilitation. The respondents in this study were 160 former drug users. The measuring instrument used to measure social support in this research isThe Social Provision Scalewhich was developed by Cutrona and Russell and has been adapted. Another measuring tool used to measure resilience is the Resilience Quotient (RQ) which was developed by Reivich and Shatte.These two measuring instruments have a reliability value of 0.803 for the social support variable and 0.826 for the resilience variable. The results of this study show that there is a positive relationship between social support and resilience in drug addicts of 0.583 (r = .583; P = 0.000). This means that if drug addicts undergoing rehabilitation have high social support, then their resilience will be high, and conversely if their social support is low then their resilience will also be low.